1992
DOI: 10.1002/pen.760321004
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of antioxidant loss from polyolefins in hot‐water applications. I: Model and application to medium density polyethylene pipes

Abstract: This paper is the first in a series of related papers describing the application of a diffusion/reaction model to the loss of antioxidants from polyolefins in hot‐water applications. The model, which is derived in detail, describes the time evolution of antioxidant concentration profiles in the exposed material in terms of adjustable parameters. The parameters describe the rates of diffusion, evaporation, extraction, and chemical reaction of antioxidant. Parameter values are determined by least‐squares fitting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(26 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…Lifetime prediction with this complex scenario is still largely based on empirical methods and is concerned only with the assessment of the time for depletion of the antioxidant system [4]. Dear and Mason [2] attempted a more rigorous method using the diffusion-reaction model developed by Smith et al [19]. It is not however clear whether this model is useful, in view of the large number of adjustable parameters to be fitted.…”
Section: Introductionmentioning
confidence: 99%
“…Lifetime prediction with this complex scenario is still largely based on empirical methods and is concerned only with the assessment of the time for depletion of the antioxidant system [4]. Dear and Mason [2] attempted a more rigorous method using the diffusion-reaction model developed by Smith et al [19]. It is not however clear whether this model is useful, in view of the large number of adjustable parameters to be fitted.…”
Section: Introductionmentioning
confidence: 99%
“…According to Gedde et al [16][17][18][19] the consumption of stabilizers by chemical reactions can be neglected, the largest loss is usually caused by leaching. Pfahler [20,21] also showed that in the presence of water migration and loss depends on the chemical structure of the stabilizer; the use of additives with smaller molecular mass often leads to shorter lifetimes, because of faster evaporation or leaching [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Gedde and Ifwarson [26] aged PEX water pipe with a hoop stress of 2.62 MPa, 110 C, 17,136 h exposure (chlorine free water but pH not reported) and concluded that infrared spectroscopy bands detected between 1680 and 1500 cm À1 were not related to double bonding, but were due to water sorbed into the oxidized PEX pipe wall because water absorbs near 1600 cm À1 . Smith et al [25] ''speculated'' and Viebke and Gedde [21] proposed that water molecules were sorbed into the wall of MDPE pipe during accelerated ageing because results of their antioxidant diffusion model for the internal pipe wall and external pipe wall were two orders of magnitude different (ageing conditions: 80, 95, 110 C, 0.84-2.51 MPa hoop stress, chlorine free water, pH not reported). In summary, the literature shows a precedent for water sorption in LDPE and MDPE at temperatures >50 C. No quantitative data were found for water penetration into PE during accelerated ageing experiments for HDPE resin or potable water pipe at temperatures equal to or less than 37 C. To truly understand solution effects on PE water pipe ageing, ageing solution characteristics and effect on PE water pipe oxidation should be evaluated.…”
Section: Introductionmentioning
confidence: 97%
“…Chemical interaction can be examined by immersing polymer samples in neat contaminant solution [67][68][69] or by exposing them to dilute aqueous solutions [70][71][72][73]. Most accelerated ageing techniques [7,9,11,14,16,17,22,25,43] Source: Dietrich and WheltonÓ2008 Awwa Research Foundation. Reprinted with Permission.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation